Translational uroradio-oncology Translationale Uroradioonkologie - Combs, S. E.; Debus, J. (Urologe, 2013)
Background: Recent developments and innovations in modern radiation oncology enable radiation oncologists to deliver a biologically, physically and technically stratified individualized treatment. In urological oncology, radiotherapy can be offered as a valid treatment alternative for a number of tumors, such as prostate cancer or urothelial cancer/bladder cancer. Methods: By improving the precision of radiotherapy, significant improvement in tumor control can be achieved, coupled with a reduction of the risk of treatment-related side effects. Techniques such as high precision radiotherapy and combinations of radiation and modern imaging, such as image-guided radiotherapy (IGRT) and adaptive radiotherapy (ART), make daily individually tailored treatment possible. Conclusions: In the future the biological characteristics of tumors and of normal tissue as well as molecular markers can be used for treatment stratification. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Prostate cancer; Radiation oncology; Radiation therapy; Urological oncology; Urothelial cancer